Vision dominates audition in adults but not children: a meta-analysis of the Colavita effect - Hirst, Rebecca J.; Cragg, Lucy; Allen, Harriet A. (Elsevier, 2018)
The Colavita effect occurs when participants respond only to the visual element of an audio-visual stimulus. This visual dominance effect is proposed to arise from asymmetric facilitation and inhibition between modalities. It has also been proposed that, unlike adults, children appear predisposed to auditory information. We provide the first quantitative synthesis of studies exploring the Colavita effect, combining data from 70 experiments across 14 studies. A mixed-meta-regression model was applied to assess whether the Colavita effect is influenced by methodological factors and age group tested. Studies reporting response time data were used to test for the presence of asymmetrical facilitation between modalities. Studies with adult participants yielded a medium, approaching large, effect size. Studies exploring the Colavita effect in children yielded no Colavita effect. Across adult and child studies, no methodological factors influenced the effect. Contrary to asymmetrical facilitation, response time data suggested a general slowing under bimodal conditions. These findings suggest that whilst vision dominates in adults, this effect is absent in childhood.